Gender Differences and Learning Outcomes Using the Ethno-PJBL Model - Astuti, Dwi Setyo; Putri, Galuh Septiani (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Biology learning in the 21st century is a challenge for teaching staff in guiding students in developing their abilities in accordance with the 4Cs and will produce competent students. One learning model that integrates 4C is project-based learning (PjBL) which is oriented to ethnoscience. The aim of this research is to determine gender differences in the implementation of ethno-PjBL learning. The research method is descriptive quantitative. Data analysis uses the Rasch model to analyze the suitability of the items to the model used and the t-test to determine the difference in cognitive scores of male and female students. The research results show that there are differences in learning outcomes between men and women. The average score for male is 68 and female is 73.5. The Levene Test results show 0.591 > 0.05, which indicates that the two gender groups have different learning outcomes. Male students complete assignments more quickly, tend to focus on content and are less interested in ethnoscience material, but their learning outcomes are no better than female students. Female students take longer to complete project assignments than male students. Female students are more interested in contextual learning presented through ethnoscience and structured design assignments through PjBL.